Reconstruction Of Indonesian Contract Law Toward Substantial Justice - Auliah Ambarwati; Anggi Sri Haryati Simarmata; Afnan Raodah (Universitas Negeri Semarang, 2026)
Indonesian contract law, rooted in the Civil Code (Kitab Undang-Undang Hukum Perdata / KUH Perdata) inherited from the Dutch colonial era, has long prioritized freedom of contract and formal legal certainty. However, this paradigm frequently overlooks structural inequalities between contracting parties, rendering contracts susceptible to becoming instruments of legalized injustice. This article aims to examine the reconstruction of Indonesian contract law toward substantial justice through four strategic steps: (1) reinterpretation of the principle of freedom of contract, bounded by propriety, balance, and good faith; (2) strengthening of the principle of balance as a corrective mechanism against the unequal positioning of parties; (3) substantive revitalization of good faith as an animating principle throughout all phases of the contractual relationship; and (4) expansion of the judicial role as an active guardian of justice. This research employs a normative legal method with statutory, conceptual, and comparative approaches. Primary legal materials include the Civil Code, court decisions, and relevant legislation, while secondary legal materials encompass scholarly literature and national as well as international legal journals. The findings indicate that true contractual justice cannot be measured solely by the existence of formal consent, but must be assessed against whether the substance and process of contract formation are genuinely fair, balanced, and respectful of the dignity of all parties. A reconstruction of contract law that integrates substantial justice will transform it from a mere instrument of formal certainty into a genuine means of realizing a more just and dignified society.